2017
DOI: 10.1016/j.jedc.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo procedure for checking identification in DSGE models

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 15 publications
(13 reference statements)
2
20
0
Order By: Relevance
“…The Taylor rule coefficient of output and inflation, elasticity of demand for exports and imports are consistent with a lot of authors' estimations, e.g. Christiano et al (2005), Smets and Wouters (2007) and Le et al (2013). Table 6 shows the persistence 12 and volatility 13 of the shocks after estimation.…”
Section: Assessing the Fit Of The Estimated Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…The Taylor rule coefficient of output and inflation, elasticity of demand for exports and imports are consistent with a lot of authors' estimations, e.g. Christiano et al (2005), Smets and Wouters (2007) and Le et al (2013). Table 6 shows the persistence 12 and volatility 13 of the shocks after estimation.…”
Section: Assessing the Fit Of The Estimated Modelsupporting
confidence: 85%
“…The estimation by indirect inference chooses the parameters of the DSGE model in a way that the simulated model generates estimates of the auxiliary model that is similar to those obtained from the data. Le et al (2013) found that using indirect inference is useful when identification is in doubt. Their numerical procedure found the DSGE model study of Smets and Wouters (2003) to be over-identified and a three equation New Keynesian model similar to Clarida, Gali and Gertler (1999) was identified.…”
Section: Model Evaluation By Indirect Inferencementioning
confidence: 99%
“…In other words, the model is not identified. Canova and Sala (2009) and Le et al (2012) have provided examples of the lack of identification of DSGE models in the New Keynesian model, see also Appendix 1. In response to such concerns various efforts have been made to establish whether various prominent DSGE macro models are identified.…”
Section: Identificationmentioning
confidence: 99%
“…One avenue has been to use the rank condition which tests whether, with no limits on data availability, a DSGE model's parameters can be uniquely discovered -Iskrev (2010), Komunjer and Ng (2011), Qu and Tkachenko (2012). Another avenue is to use indirect inference in the way suggested by Le et al (2017). These two methods establish 'precise' identification -i.e.…”
Section: Identificationmentioning
confidence: 99%
“…Le et al (2013) examined this issue for a three-equation New Keynesian model of the sort being considered here. They found that it was likely to be heavily over-identified.…”
Section: Model Identificationmentioning
confidence: 99%